Solvent free synthesis of polyaniline with improved molecular weight through solid state mechanochemical milling at ambient temperature. (February 2013) - Zhou, Z. H.; Zhang, X. X.; Tian, D.; Xiong, R.; Lu, C. H.
Abstract : Mechanochemical synthesis of polyaniline was conducted by our self-designed pan mill equipment, which has a unique and smart structure and can exert fairly strong squeezing and shearing forces on the milled materials. The obtained product was examined by SEM, Fourier transform infrared (FTIR) and UV–Vis spectroscopy, viscometric average molecular weight measurement, X-ray diffraction (XRD) and thermogravimetric analysis. Comparative analysis of polyaniline prepared by solid state mechanochemical milling and mortar grinding was carried out. The formation of polyaniline was confirmed by FTIR and UV–Vis spectroscopy. Measurement of viscosity molecular weight showed that the molecular weight of pan milling prepared polyaniline was over three times higher than that of the mortar ground ones. The analysis of XRD patterns showed that polyaniline exposed to longer time shearing force tends to have a higher degree of crystallinity, and after milling for a certain time, pan milling prepared polyaniline would be more crystalline than the mortar ground polyaniline. Enhanced thermal stability of the pan milling prepared polyaniline further confirmed the improvement of the molecular weight.